Duplication of the abducens nerve at the petroclival region: An anatomic study - Ozveren, MF; Sam, B; Akdemir, I; Alkan, A; Tekdemir, I; Deda, H (Lippincott Williams & Wilkins, 2003)
OBJECTIVE: During its course between the brainstem and the lateral rectus muscle, the abducens nerve usually travels forward as a single trunk, but it is not uncommon for the nerve to split into two branches. The objective of this study was to establish the incidence and the clinical importance of the duplication of the nerve. METHODS: The study was performed on 100 sides of 50 autopsy materials. In 10 of 11 cases of duplicated abducens nerve, colored latex was injected into the common carotid arteries and the internal jugular veins. The remaining case was used for histological examination. RESULTS: Four of 50 cases had duplicated abducens nerve bilaterally. In seven cases, the duplicated abducens nerve was unilateral. In 9 of these 15 specimens, the abducens nerve emerged from the brainstem as a single trunk, entered the subarachnoid space, split into two branches, merged again in the cavernous sinus, and innervated the lateral rectus muscle as a single trunk. In six specimens, conversely, the abducens nerve exited the pontomedullary sulcus as two separate radices but joined in the cavernous sinus to innervate the lateral rectus muscle. In 13 specimens, both branches of the nerve passed beneath the petrosphenoidal ligament. In two specimens, one of the branches passed under the ligament and the other passed over it. In one of these last two specimens, one branch passed over the petrosphenoidal ligament and the other through a bony canal formed by the petrous apex and the superolateral border of the clivus. in all of the specimens, both branches were wrapped by two layers: an inner layer made up of the arachnoid membrane and an outer layer composed of the dura during its course between their dural openings and the lateral wall of the cavernous segment of the internal carotid artery. This finding was also confirmed by histological examination in one specimen. CONCLUSION: Double abducens nerve is not a rare variation. Keeping,such variations in mind could spare us from injuring the Vlth cranial nerve during cranial base operations and transvenous endovascular interventions.
Keywords: abducens nerve; arachnoid membrane; duplication; dura mater; petrosphenoidal ligament